Pengaruh Profitabilitas, Struktur Kepemilikan dan Pertumbuhan Perusahaan terhadap Kebijakan Dividen Pada Perusahaan Manufaktur - Natalia Lembu Nai; Gendro Wiyono; Alfiatul Maulida (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Dividen policy is a descision making regarding the distribution of profits earned by the company, whether it will be distributed to shareholders or will be retained in the form of retained earnings to finance investments in the future. This study aims to examine the effect of Profitability, Ownership Structure and Company Growth Rate on Dividend Policy in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Samples were taken from as many as 43 companies. In this study, Profitability is proxied by using return on equity (ROE), Ownership Structure is proxied by Managerial Ownership (KM) and Company Growth is proxied by total asset growth (Growth). The sampling method used in this research is a purposive sampling method. The analytical method used in this research is descriptive statistical test, classical assumption test and multiple regression analysis test using the SPSS application. The results showed that the independent variables, namely profitability, ownership structure and company growth had a positive and significant effect on the dividend payout ratio. Keywords: Profitability, Ownership Structure, Company Growth, Dividend Policy